A Feasibility Study on an Automotive Service Center in the Scout Area - Tulao, Joselito R.; Villegas, Michael G.; Yu, Lawrence L.; Polina, Annah Karina D. (College of Engineering, 1993)
The project is about the setting up of an auto repair shop in the Scout Area. Its objective is to determine whether the said project will be feasible in terms of the market, technical and financial aspects. The proposed service shop is called C.A.R.S. which stands for 'Convenient Auto Repair Shop'. Among its features as the names implies is convenience in terms of workmanship quality, fast and personalized services, and its array of modern equipments. The said facility caters to Quezon City vehicle owners, particularly those in the Scout Area and surrounding places. Results of the market study shoes that although a modern auto repair shop is not entirely a new concept; a big percentage of customers will be willing to try the said establishment. Among the reasons mentioned by several car owners, price and quality proved to be the primary factors. With regards to its competitors it was also discovered that gasoline stations and ordinary repair shops are the most frequented by customers seeking auto repair services. But with the amount of vehicle owners unsatisfied and unserviced by most of these competitors, a potential market for an auto repair shop is promising. C.A.R.S. boasts of modern equipments and unique services that are not present in common repair shops. Purchase and installation of these equipments are made through import distributors like Tensorex and Mancor. They are sold at reasonable prices and are delivered as soon as the equipment is in stock. The availability of suppliers mentioned above makes the project technically feasible. The presence of high technology materials plus the rather expensive facilities of the structure made the pre-operating expenses costly. But based on the conservative future projections, these expenses can easily be recovered within a five year period. Computations also showed that Return on Investments will range from 20 to 22 percent for the coming years with an increasing trend. Although centered on financial profitability, the project did not fail to contribute some socio-economic benefits. Employment of workers and payment of taxes are basically its contributions. The only benefit is that it will not be of help to Filipino manufacturers since spare parts used for repairs are all imported.